The Colour Magnitude Diagram of The Galactic Cluster NGC 6383 - Pik Sin The (Journal of Mathematical and Fundamental Sciences, 1965)
Abstract. Almost all the stars in a circular area with  a radius of  about 12 min. of arc, were measured photometrically down to V="13".80 mag., using plates obtained with the Uppsala Schmidt telescope Mt. Stromlo and the Schmidt telescope  at Lembang. The photographic measurement generally confirm  Enggen's remarkable result that NGC 6383 is a very young cluster, similar to NGC 2264. Groups stars lying on different parts of the colour magnitude diagram  NGC 6383, are discussed in connection with Herbig's idea about non-coevalness of stars in stellar cluster. Ichtisar. Hampir semua bintang dalam sebuah daerah bundar dengan djari2 kira2 12 menit busur, telah diukur setjara photometris sampai V = 13.80 magn., dengan menggunakan katja2 potret jang didapatkan dengan teropong Schmidt Uppsala di Observatorium Mt. Stromlo dan teropong Schmidt di Lembang. Kumpulan2 bintang jang terletak pada tempat2 jang berbeda-beda pada diagram warna magnitudo daripada NGC 6383 telah dibahas sehubungan dengan idee Herbig mengenai tidak dilahirkannja bintang2 dalam sebuah gugus bintang pada saat bersamaan.